2014
DOI: 10.1016/j.ophtha.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Color Vision Deficiency in Preschool Children

Abstract: Purpose To determine the sex- and ethnicity-specific prevalence of color vision deficiency (CVD) in black, Asian, Hispanic, and non-Hispanic white preschool children. Design Population-based, cross-sectional study. Participants The Multi-Ethnic Pediatric Eye Disease Study is a population-based evaluation of the prevalence of vision disorders in children in Southern California. A total of 5960 subjects 30 to 72 months of age were recruited for the study, of whom 4177 were able to complete color vision testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…In the present study the percentage of colour vision deficiency was higher among boys (3.6%) as compared to girls (0.6%). This finding is supported by several studies [ 1 , 13 , 20 , 21 ]. While other studies [ 3 , 16 , 19 ] showed that colour blindness was found only among the males.…”
Section: Main Textsupporting
confidence: 86%
“…In the present study the percentage of colour vision deficiency was higher among boys (3.6%) as compared to girls (0.6%). This finding is supported by several studies [ 1 , 13 , 20 , 21 ]. While other studies [ 3 , 16 , 19 ] showed that colour blindness was found only among the males.…”
Section: Main Textsupporting
confidence: 86%
“…While we used the color system to draw attention and aid in comprehension, we also provided labels to the categories so a color-blind individual could comprehend their risk level. Given the low prevalence of this disorder, specifically in women [ 40 ] who represent 80% of patients undergoing DXA, we feel that using this coloring system would be mostly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Tools, such as the websites http://color.adobe.com/create or coolors.co, are useful to generate color schemes. It should be emphasized, however, that use of color should account for readers with color blindness, which affects up to 5.6% of individuals 16 . Although color can add emphasis and tone to an infographic, it should not be used to convey a message as meaning may be lost to individuals who cannot perceive that information.…”
Section: Principles Of Infographic Designmentioning
confidence: 99%